THE EFFECT OF TAXPAYER AWARENESS, MORAL RESPONSIBILITY, EFFECTIVENESS PROGRAMME OF SAMSAT BULAT, AND PERCEPTIONS OF FISCUS SERVICE PERFORMANCE ON MOTOR VEHICLE TAXPAYER COMPLIANCE - Asep Kurniawan; Indah Umiyati; Inggit Aprilia (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2022)
This study aims to determine the effect of taxpayer awareness, moral obligation, effectiveness of the mobile samsat program, and perceptions of tax service performance on taxpayer compliance in the Karawang Regency area. This type of research uses a quantitative approach with convenience sampling technique. The data used in this study is primary data in the form of questionnaires distributed to motorized vehicle taxpayers in the Karawang Regency area. This study uses multiple linear analysis and regression models using the classical assumption test. The results of partial hypothesis testing prove that the moral obligation and effectiveness of the mobile Samsat program have a positive and significant effect on motor vehicle taxpayer compliance. Meanwhile, taxpayer awareness and perception of tax service performance have no significant effect on motor vehicle taxpayer compliance. The results of the study simultaneously show that taxpayer awareness, moral obligation, effectiveness of the mobile samsat program, and perceptions of tax service performance have a positive and significant effect on motor vehicle taxpayer compliance with a coefficient of determination of 35.2% while the remaining 64.8% is explained by other factors not examined.